2018
DOI: 10.1159/000494277
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Prediction of Tumor Invasion Depth in Early Gastric Signet Ring Cell Carcinoma

Abstract: Introduction: Signet ring cell carcinoma (SRC) is a poorly differentiated cancer of the stomach. Recent studies imply that early gastric SRC can be well managed by endoscopic resection. Unfortunately, unlike differentiated cancers, the endoscopic features of early gastric SRC have not been well studied. This study evaluated the endoscopic features of early gastric SRC, as well as the risk factors for submucosal (SM) invasion. Method: The medical records of patients from 7 tertiary hospitals (Daejeon and Chungc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Through logical regression analysis, Kang et al. ( 24 ) revealed that scar deformity, nodular surface appearance, and surface depression tended to invade SM2 for early SRC (OR 3.4, 5.9, 6.0; p < 0.05). For UD EGC patients with non-curative ESD, Jie-Hyun Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…Through logical regression analysis, Kang et al. ( 24 ) revealed that scar deformity, nodular surface appearance, and surface depression tended to invade SM2 for early SRC (OR 3.4, 5.9, 6.0; p < 0.05). For UD EGC patients with non-curative ESD, Jie-Hyun Kim et al.…”
Section: Discussionmentioning
confidence: 99%